ANALISIS EFEKTIFITAS PADA MESIN EXTRUDER (CY65-II) MENGGUNAKAN PENDEKATAN KONSEP TOTAL PRODUCTIVE MAINTENANCE DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN SIX BIG LOSSES DI PT. ABC - Andini Lusiana Permata Sari, (2021)
Maintenance on machines is very important to maintain engine performance so that production targets will be met. PT. ABC is a company that moves its business in the food industry, especially snacks. Based on observations in the production field and the results of interviews with the Head of Production at PT. ABC in 2021, there was a machine that experienced a breakdown in the production of sweet milk cream snack, namely the Extruder machine (CY65-II) which resulted in many defective products. The purpose of this research is to determine the level of machine effectiveness with OEE, identify the factors causing time losses with Six Big Losses, and provide suggestions for improvements based on the analysis of the processed data and the design through ProModel simulation. This research was conducted using Overall Equipment Effectiveness, Six Big Losses, Pareto Diagrams, Fishbone Diagrams, and continued with simulations using ProModel software. The results show that the average value of OEE in September 2020-January 2021 is 68.28% which means it is still below the JIPM standard, which is 85%, the highest percentage value for the six big losses is obtained from the Idling and minor stoppages factor of 30.95%, and the proposed improvements are in the form of changing the work system to 5-2, namely a decrease in average production output from 10352 to 7396 boxes with a percentage decrease in output of 28.55% and it can reduce overproduction with a value of 26.83%.